2013
DOI: 10.3390/md11093209
|View full text |Cite
|
Sign up to set email alerts
|

Marine Derived Hamacanthins as Lead for the Development of Novel PDGFRβ Protein Kinase Inhibitors

Abstract: In this study, we report on pyrazin-2(1H)-ones as lead for the development of potent adenosine triphosphate (ATP) competitive protein kinase inhibitors with implications as anti-cancer drugs. Initially, we identified the pyrazin-2(1H)-one scaffold from hamacanthins (deep sea marine sponge alkaloids) by Molecular Modeling studies as core binding motif in the ATP pocket of receptor tyrosine kinases (RTK), which are validated drug targets for the treatment of various neoplastic diseases. Structure-based design st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…www.nature.com/aps Nair DG et al Acta Pharmacologica Sinica npg leagues showed the inhibitory effects of the pyrazin-2(1H)-one scaffold from hamacanthins, which were also isolated from a marine sponge and are highly potent in binding and inhibiting PDGFR-β [51] . Based on the outstanding role of the PDGF system in liver fibrosis, it will be extremely worthwhile to study the effects of these molecules on the setting of experimental liver disease models.…”
Section: Substances Isolated From Spongesmentioning
confidence: 98%
See 1 more Smart Citation
“…www.nature.com/aps Nair DG et al Acta Pharmacologica Sinica npg leagues showed the inhibitory effects of the pyrazin-2(1H)-one scaffold from hamacanthins, which were also isolated from a marine sponge and are highly potent in binding and inhibiting PDGFR-β [51] . Based on the outstanding role of the PDGF system in liver fibrosis, it will be extremely worthwhile to study the effects of these molecules on the setting of experimental liver disease models.…”
Section: Substances Isolated From Spongesmentioning
confidence: 98%
“…D'Orazio et al, 2012 [34] Takamatsu et al, 2003 [87] Takamatsu et al, 2003 [87] Silva et al, 2012 [88] D'Orazio et al, 2012 [34] Yeh et al, 2012 [89] He et al, 2013 [90] Liu et al, 2012 [47] Esmat et al, 2013 [30] Althunibat et al, 2013 [91] Zhou et al, 2012 [92] Balaji et al, 2004 [45] Pereira et al, 2011 [82] Hong et al, 2012 [93] Liaw et al, 2010 [94] Baidu et al, 2010 [95] Esmat et al, 2013 [33] Whitehouse & Fairlie [96] Kossuga et al, 2008 [97] Kobayashi et al, 2007 [98] Choi et al, 2013 [50] Pinchuk et al, 2013 [51] Tong et al, 2005 [52] Ku et al, 2013 [99] Huang et al, 2007 [100] Posadas et al, 2013 [101] Posadas et al, 2013 [101] Nagle et al, 2004 [102] Catassi et al, 2006 [103] Sun et al, 2007 [39] Kang et al, 2013 [104] Chao et al, 2008 [105] Cheng et al, 2008 [106] …”
mentioning
confidence: 99%
“…It is noteworthy that structural modifications of these natural products had led to synthetic analogs with DNAquadruplex recognition, 4 antibacterial, 5,6 antilesihmanial, 7 antitumoral, [8][9][10][11] and angiogenesis inhibition 12 activity. Most of these compounds are linked through the indole C3 position, with only a few exceptions such as Gelliusines F which is a C2-C3 linked bis-indole.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of hamacanthin-derived pyrazin-2(1H)-ones have shown interesting properties as lead for the further development of highly potent and selective PDGFRβ-inhibitors. Modeling studies showed the core moiety of hamacanthins to bind in the ATP binding pocket of the receptor tyrosine kinase, and suggested a straightforward strategy towards potent PDGFRβ binders [93].…”
Section: Compounds That Inhibit the Activation Of The Angiogenic Switchmentioning
confidence: 99%